Synergistic effect of the association of methyl divanillate with chemotherapy in triple negative breast cancer cells - Pessôa, Adriano de Souza (2025)
Triple-negative breast cancer (TNBC) is defined by its aggressive phenotype and lack of specific therapeutic targets. This study investigated the isolated and combined effects of methyl divanillate (DMV) and doxorubicin (DOX) in 2D and 3D TNBC models through proteomic and functional analyses. DMV broadly modulated pathways related to energy metabolism, proteostasis, translation, and cell adhesion, prominently suppressing ribosomal proteins (RPLs, RPSs), chaperones (HSPA5, HSP90AB1), and glycolytic enzymes (ALDOA, GAPDH, LDHA). These changes resulted in inhibition of protein synthesis, endoplasmic reticulum stress, and collapse of redox balance. The DMV/DOX combination amplified oxidative stress and mitochondrial dysfunction, promoting synergistic cytotoxicity and pronounced structural disruption. Comparative analyses revealed greater cytoskeletal fragmentation and migration inhibition in MDAMB-231, while HCC70 exhibited partial compensatory remodeling. In 3D cultures, DMV induced deeper metabolic and proteostatic deregulation closely mimicking tumor microenvironment conditions. TAGLN2 emerged as a potential biomarker of response and mediator of DMV-induced structural vulnerability. Collectively, the findings demonstrate that DMV acts as a systemic modulator of tumor vulnerability by impairing redox homeostasis, proteostasis, and cytoskeletal integrity, thereby sensitizing cells to oxidative and genotoxic stress. These results position DMV as a promising candidate for combined and personalized therapeutic strategies in TNBC.